Retnla overexpression attenuates allergic inflammation of the airway. - Mi-Ran Lee; Dahee Shim; Jihye Yoon; Hyung Seok Jang; Se-Woong Oh; Suk Hyo Suh; Jae-Hoon Choi; Goo Taeg Oh (PLoS ONE, 2014)
Resistin-like molecule alpha (Retnla), also known as 'Found in inflammatory zone 1', is a secreted protein that has been found in bronchoalveolar lavage (BAL) fluid of ovalbumin (OVA)-induced asthmatic mice and plays a role as a regulator of T helper (Th)2-driven inflammation. However, the role of Retnla in the progress of Th2-driven airway inflammation is not yet clear. To better understand the function of Retnla in Th2-driven airway inflammation, we generated Retnla-overexpressing (Retnla-Tg) mice. Retnla-Tg mice showed increased expression of Retnla protein in BAL fluid and airway epithelial cells. Retnla overexpression itself did not induce any alteration in lung histology or lung function compared to non-Tg controls. However, OVA-sensitized/challenged Retnla-Tg mice had decreased numbers of cells in BAL and inflammatory cells accumulating in the lung. They also showed a reduction in mucus production in the airway epithelium, concomitant with a decreased Muc5ac level. These results were accompanied by reduced levels of Th2 cytokines, including interleukin (IL)-4, IL-5, and IL-13, with no effect on levels of OVA-specific immunoglobulin isotypes. Furthermore, phosphorylation of ERK was markedly reduced in the lungs of OVA-challenged Retnla-Tg mice. Taken together, these results indicates that Retnla protects against Th2-mediated inflammation in an experimental mouse model of asthma, suggesting that therapeutic approaches to enhance the production of Retnla or Retnla-like molecules could be valuable for preventing allergic lung inflammation.